(untitled) (Cadernos de Sociomuseologia, 2009)
The guidelines presented in this document are a preliminary strategy for establishing a comprehensive policy for the needs of training and education wiyhin the sector and adjoining areas, across fields of knowledge and professions concerned, on relevant levels and for the varies institutions and operators. The objective of these guidelines is to analysis the problems, objectives and goals for development of a far reaching system of educational and training programs and courses for museums, cultural heritage and related fields of activities. This objective comprises a close collaboration between museum, cultural heritage organizations and educating organizations, notably within universities and colleges, but also other kinds of educating bodies.